Occurrence of Postictal α/β Activity During Maintenance Course of Electroconvulsive Therapy. Issue 4 (December 2015) - Schultz, Krista; Tham, Joseph; Chan, Peter; Brenner, Colleen; Northcott, Colleen; Vila-Rodriguez, Fidel
Abstract : Abstract: We are aware of a report of postictal α activity after seizures in Epilepsy and Behavior . We would like to report another case of a similar phenomenon in a woman receiving maintenance electroconvulsive therapy.